From seabed to sickbed: lessons gained from allorecognition in marine invertebrates - Rinkevich, Baruch (Frontiers in Immunology, 2025)
Despite decades of progress, long-term outcomes in human organ transplantation remain challenging. Functional decline in transplanted organs has stagnated over the past two decades, with most patients requiring lifelong immunosuppression, therapies that overlook the principles of self/non-self recognition and natural transplantation events in humans. To address these discrepancies, this perspective proposes that immunity evolved not as pathogen-driven but as a mechanism to preserve individuality by preventing invasion from parasitic conspecific cells. It further reveals that the concept of “self/non-self” recognition encompasses multiple theories with complex and often ambiguous terminology, lacking precise definitions. In comparisons, natural historecognition reactions in sessile marine invertebrates are regulated by a wide spectrum of precise and specific allorecognition systems, with transitive and non-transitive hierarchies. Using the coral Stylophora pistillata and the ascidian Botryllus schlosseri as models, it is evident these organisms distinguish ‘self’ from ‘non-self’ with remarkable accuracy across various allogeneic combinations, identifying each non-self entity while simultaneously recognizing selfhood through transitive allogeneic hierarchies. Their allorecognition offers an improved explanation for post-transplant outcomes by accounting for the natural dynamic, spatiotemporal evolution of selfhood. To bridge natural (in invertebrates and humans alike) and clinical transplantation phenomena, the ‘allorecognition landscape’ (AL) metaphor is proposed. This unified framework conceptualizes self/non-self recognition as shaped by two dynamic continuums of ‘self’ and ‘non-self’ nature. Throughout the patient lifespan, the AL represents diverse and transient arrays of specific ‘self’ and ‘non-self’ states (including reciprocal states) that shift over time in either recognition direction, requiring adaptable clinical strategies to address their evolving nature.